Questions descriptions macrostructures vocabulary (Philological Studies: Scientific Bulletin of Kryvyi Rih State Pedagogical University, 2014)
The article discusses approaches to the description of lexical structure. Discusses the principles of scientific and naive categorization. Interprets the lexical-semantic category. The essence of the semantic relations, organizing large groups of words.
Keywords: lexicology; the value paradigms; syntagmatics; categorization; word classes; lexical and semantic fields